INDUCTION OF DROUGHT RESISTANCE IN MELON (Cucumis melo L.) M15 WITH HORMOPRIMING BRASSINOSTEROID BASED ON MORFOLOGY, ANATOMY, AND PHYSIOLOGY ASPECTS - Rifki, Arif Nur Rifki; Solichatun; Pitoyo, Ari (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2024)
Melon productivity in Indonesia has been declining. Global climate change is affecting the productivity of melons. Long-term droughts have contributed to a reduction in plant growth and development. Hormopriming is an alternative to increase the germination and growth of melon plants by soaking seeds in a solution of plant growth regulators. Brassinosteroid can enhance germination and plant tolerance under drought conditions. The objective of this research is to examine the impact of brassinosteroid hormopriming treatment on the germination and growth of melon plants subjected to various degrees of drought stress. The study utilized a two-factor fully randomized design. The brassinosteroid concentrations used were 0, 0.05, 0.10, and 0.15 ppm. Media with different water capacities of 75%, 50%, and 25% Space Capacity (SC) were used to test drought stress resistance. Water capacities were examined using the gravimetric method. This study's findings suggest that treating melon plants with brassinosteroid variations can induce drought resistance in M15 melons. A brassinosteroid concentration of 0.15 ppm is the best concentration, as it can increase all parameters of plant growth and adaptation under each variation of water availability provided. The findings of this study can serve as a reference for melon cultivators constrained by dry land conditions to increase the efficiency of cultivation.